CONSIDERATIONS ON BUSINESS AND TRADE NEGOTIATION - ALEXANDRU CRISTIAN DOBRE (Annals of the University of Petrosani: Economics)
Business and negotiations have always been a preocupation of people since old times. Large profit can be obtained by an individual or company if others maintain their view. The development of global economic networks has increased the need for negotiations between people of different environments and cultures. The thechnological developments and digitalization have also made changes in traditional negotiation strategies. Now as more as ever, negotiations are being made through online exchanges. In this paper we try to outline a consideration on how to achieve win-win negotiations and what kind of principles we can use for a succesful negotiation process. We also try to analyze the advantages and disatvantages of online email negotiations. In the end we propose a couple of exercises for increasing negotiation expertise and finalize with our conclusions regarding the subject matter.